The impact of preoperative immunonutritional status on prognosis in ovarian cancer: a multicenter real-world study - Xingyu Liu; Ming Li; Yingjun Zhao; Xiaofei Jiao; Yang Yu; Ruyuan Li; Shaoqing Zeng; Jianhua Chi; Guanchen Ma; Yabing Huo; Zikun Peng; Jiahao Liu; et al. (Journal of Ovarian Research)
Abstract Background To investigate the effect of preoperative immunonutritional status on prognosis in epithelial ovarian cancer patients. Methods A multicenter real-world study included 922 patients with histologically confirmed epithelial ovarian cancer who received comprehensive staged surgery or debulking surgery at seven tertiary hospitals in China between 2012 and 2023. Prognostic nutritional index (PNI) and systemic immune-inflammation index (SII) were used to assess the immunonutritional status for their superior predictive power to indicate the nutritional status and the inflammatory immunity. Cox regression analyses were employed to identify variables associated with progression-free survival (PFS) and overall survival (OS). Results In the early-stage cohort of 224 epithelial ovarian cancer patients, the optimal cut-off value for PNI was 47.47 for both PFS and OS, while the optimal cut-off value for SII values were 551.37 for PFS and 771.78 for OS. In the late-stage group of 698 patients, the optimal PNI thresholds were 47.76 for PFS and 46.00 for OS, with SII values of 720.96 for PFS and 1686.11 for OS. In multivariate analysis of early-stage patients, high PNI was an independent protective factor for PFS (hazard ratio (HR), 0.39 (95% confidence interval (CI) 0.20–0.76), P = 0.006) and OS (HR, 0.44 (95% CI 0.20–0.97), P = 0.042), respectively. High SII was significantly associated with PFS (HR, 2.43 (95% CI 1.23–4.81), P = 0.011) and marginally unfavorable for OS (HR, 2.05 (95% CI 0.96–4.39), P = 0.064). In advanced population, PNI (HR, 0.77 (95% CI 0.60–0.99), P = 0.043) and SII (HR, 1.34 (95% CI 1.01–1.78), P = 0.041) were independent prognostic factors for OS but had no impact on PFS (P = 0.185, P = 0.188, respectively). Conclusion Poor preoperative immunonutritional status has a deleterious effect on the prognosis of patients with ovarian cancer. Intervention in patients suffering from suboptimal preoperative immunonutritional status may facilitate improved survival outcomes.